Vapor Cannabis Exposure Generationally Affects Male Reproductive Functions in Mice. (2nd December 2021) - Shi, Mingxin; Langholt, Esther M; Butler, Logan C; Harvey, Madeleine E; Wheeler, Emma C; Zhao, Liang; MacLean, James A; Oh, Yeongseok; Sabrowsky, Emily; Yu, Sue; Watson, Shane; Davis, Jon F; et al.
Abstract: This study was performed to examine whether vapor exposure to cannabis plant matter negatively impacts male reproductive functions and testis development in mice. Adult CD-1 male mice (F0) were exposed to air (control) or 200 mg of vaporized cannabis plant matter 3×/day over a 10-day period. Subsequently, F0 males were bred with drug-naïve CD-1 females to generate F1 males, and F1 offspring were used to generate F2 males. Cannabis vapor exposure decreased sperm count and/or motility in F0 and F1 males and disrupted the progression of germ cell development, as morphometric analyses exhibited an abnormal distribution of the stages of spermatogenesis in F0 males. Although plasma levels of testosterone were not affected by cannabis exposure in any ages or generations of males, dysregulated steroidogenic enzymes, Cyp11a1 and Cyp19a1, were observed in F0 testis. In the neonatal testis from F1 males, although apoptosis was not altered, DNA damage and DNMT1, but not DNMT3A and DNMT3B, were increased in germ cells following cannabis exposure. In contrast, the alterations of DNA damage and DNMT1 expression were not observed in F2 neonatal males. These results suggest that cannabis vapor exposure generationally affects male reproductive functions, probably due to disruption of spermatogenesis in the developing testis.